Lack of Maternal Glutamate Cysteine Ligase Modifier Subunit (Gclm) Decreases Oocyte Glutathione Concentrations and Disrupts Preimplantation Development in Mice - Nakamura, Brooke N. (Endocrine Society, 2011)
Glutathione (GSH) is the most abundant intracellular thiol and an important regulator of cellular redox status. Mice that lack the modifier subunit of glutamate cysteine ligase (Gclm), the rate-limiting enzyme in GSH synthesis, have decreased GSH synthesis. Nicotinamide nucleotide transhydrogenase, an inner mitochondrial membrane protein, catalyzes the interconversion of reduced nicotinamide adenine dinucleotide and reduced nicotinamide adenine dinucleotide phosphate; reduced nicotinamide adenine dinucleotide phosphate is required for reduction of GSH disulfide. Previous work supports roles for GSH in preimplantation development. We hypothesized that Gclm−/− mice have increased preimplantation embryonic mortality and that this effect is enhanced by absence of a functioning Nnt gene. Gclm−/− females produced significantly fewer pups per litter than Gclm+/+ littermates. Numbers of oocytes ovulated in a natural estrous cycle or upon superovulation did not differ by genotype. Fewer uterine implantation sites were observed in the Gclm−/− females. Prepubertal Gclm−/− and Gclm+/+ females were superovulated, then mated overnight with a Gclm+/+ male. At 0.5 d postcoitum, Gclm−/− females had significantly lower percentages of zygotes with two pronuclei and higher percentages of zygotes with one pronucleus than Gclm+/+ or Gclm+/− females. At 3.5 d postcoitum, a significantly lower percentage of blastocyst stage embryos was recovered from uteri of Gclm−/− females than Gclm+/+ females. Embryonic development to the blastocyst stage, but not the two-cell stage, was significantly decreased after in vitro fertilization of oocytes from Gclm−/− females compared with Gclm+/+ females. The Nnt mutation did not enhance the effects of Gclm genotype on female fertility. These results demonstrate critical roles for maternal GSH in supporting normal preimplantation development.